Robotic distal gastrectomy using a novel pre-emptive supra-pancreatic approach without duodenal transection in the dissection of D2 lymph nodes for gastric cancer - Xie, Jianming; Yang, Jiabin; Wang, Meixiao; Yin, Yongfang; Yan, Zhilong (Frontiers in Oncology, 2024)
Background Robot-assisted surgery has shown remarkable progress as a minimally invasive procedure for gastric cancer. This study aimed to compare the pre-emptive suprapancreatic approach without duodenal transection and the conventional approach in terms of perioperative feasibility and short-term surgical outcomes. Methods We retrospectively analyzed all patients who underwent robotic distal gastrectomy with D2 lymph node dissection using the da Vinci Xi robotic system between December 2021 and April 2023 and categorized them into two groups for comparison. Patients treated using the pre-emptive suprapancreatic approach (observation group) were compared with those who received the conventional approach (control group). Employing one-to-one propensity score matching, we evaluated the postoperative morbidity and short-term outcomes in these two distinct groups to assess the efficacy and safety of the novel surgical technique. Results This study enrolled 131 patients: 70 in the observation group and 61 in the control group. After propensity score matching, the operative times were significantly longer in the control group than in the observation group (229.10 ± 33.96 vs. 174.84 ± 18.37, p <0.001). The mean blood loss was lower in the observation group than in the control group (25.20 ± 11.18 vs. 85.00 ± 38.78, p <0.001). Additionally, the observation group exhibited a higher number of retrieved lymph nodes, including suprapyloric, perigastric, and superior pancreatic lymph nodes (28.69 ± 5.48 vs. 19.21 ± 2.89, p <0.001; 4.98 ± 1.27 vs. 4.29 ± 1.21, p = 0.012; 10.52 ± 2.39 vs. 5.50 ± 1.62, p <0.001; 6.26 ± 2.64 vs. 5.00 ± 1.72, p = 0.029). Drain amylase levels in the observation group were significantly lower than those in the control group (30.08 ± 33.74 vs. 69.14 ± 66.81, p <0.001). Conclusion This study revealed that using the pre-emptive suprapancreatic approach without duodenal transection in the dissection of D2 lymph nodes for gastric cancer is a safe and feasible procedure in terms of surgical outcomes.